2022
DOI: 10.1136/bmj-2022-070568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short term surgical outcomes of male and female gastrointestinal surgeons in Japan: retrospective cohort study

Abstract: Objective To compare short term surgical outcomes between male and female gastrointestinal surgeons in Japan. Design Retrospective cohort study. Setting Data from the Japanese National Clinical Database (includes data on >95% of surgeries performed in Japan) (2013-17) and the Japanese Society of Gastroenterological Surgery. Participants Male and female surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…3 In comparison, the percentage of female surgeons in the UK and Japan was 27% and 22%, respectively. 4,5 The practice of medicine is known to vary between female and male physicians, [6][7][8][9] but less is known about whether female and male surgeons differ in surgical techniques or outcomes. A Canadian study of 25 different surgical procedures showed a slightly decreased 30-day mortality but similar surgical outcomes in patients treated by female vs male surgeons.…”
mentioning
confidence: 99%
“…3 In comparison, the percentage of female surgeons in the UK and Japan was 27% and 22%, respectively. 4,5 The practice of medicine is known to vary between female and male physicians, [6][7][8][9] but less is known about whether female and male surgeons differ in surgical techniques or outcomes. A Canadian study of 25 different surgical procedures showed a slightly decreased 30-day mortality but similar surgical outcomes in patients treated by female vs male surgeons.…”
mentioning
confidence: 99%
“…The study conducted by Okoshi and colleagues1 supports the claim that female surgeons can achieve as good outcomes as male surgeons and raises the question of why, when most medical school entrants are women, they remain under-represented in surgical specialties. The existing literature indicates several structural barriers, such as shift patterns, lack of part time employment opportunities, and the effects of maternity leave on career progression, as well as cultural barriers, such as the belief that surgery is “an old boys’ club” and the dominant stereotype of the surgeon that comprises traditionally male characteristics 23…”
mentioning
confidence: 86%
“…6,7 Despite this, patients treated by female surgeons do as well if not better in terms of early survival, hospital readmissions, and complications. 8,9 Total cases as both lead surgeon and as lead surgeon without direct supervision (autonomous operating) have been used as a marker of quality of surgical training and readiness for indpendent practice. 10,11 It is generally expected that trainees will progress from operating as lead surgeon under supervision to operating independently, or training junior trainees for all core speciality procedures by the end of their training.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Despite this, patients treated by female surgeons do as well if not better in terms of early survival, hospital readmissions, and complications. 8,9…”
Section: Introductionmentioning
confidence: 99%